Geographical variation of organ size in Andrew’s toad (Bufo andrewsi) - Zhu, Xin; Chen, Chuan; Jiang, Ying; Zhao, Li; Jin, Long (Frontiers in Ecology and Evolution, 2022)
Phenotypic variation of morphological and physiological traits is assumed to be generated from spatial heterogeneity in environments, and it has been regarded as an important concern domain in evolutionary biology. Organs display markedly size variation among populations along environmental gradients and this variation is associated with changes in oxygen supply and energy demands. Here, we investigated geographical variation in the relative size of organs (i.e., brain, heart, lung, gallbladder, livers, spleen, kidneys, and digestive tract) among 14 populations of Andrew’s toad (Bufo andrewsi) transcending an elevational range from 864 to 2367 m, and spanning 8° latitude. We found that although the relative sizes of the eight specific organs varied significantly among populations, none organ size was affected by altitude and latitude. However, based on the combined the new data and published data we found a negative relationship between the relative size of the heart and latitude, contrasting to the Hesse’s rule. We also found that the relative size of livers was positively linked to latitude, suggesting that more energy demands and intakes due to slower metabolism in high latitude shaped the evolution of larger livers.